Igniting Curiosity: E-LKPD with a Scientific Twist on Circle Concepts - Devi Damayanti; Siti Nailul Ilmi; Indah Wahyuni; Umi Farihah (Educazione: Journal of Education and Learning, 2023)
This study aims to develop and test the effectiveness of live worksheet-based E-LKPD in increasing student involvement and understanding of circle material in grade VI elementary school. The main problem faced is the low interest of students in mathematics learning, which is monotonous and less interactive, which causes difficulties in understanding material that is considered difficult. The development of this product is based on an analysis of student needs and interviews with teachers to identify challenges in mathematics learning. The research method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, which includes the stages of needs analysis, product design, interactive media development, and product testing through limited and field trials. The results showed that E-LKPD based on live worksheets increased student motivation and material comprehension, significantly increasing learning outcomes between the pretest and post-test. These findings suggest that technology-based teaching media can increase the effectiveness of mathematics learning at the elementary school level, especially in materials that are considered difficult. The implication of this research is the development of interactive teaching media that can be applied in various educational contexts to improve the quality of learning.